Pengaruh Pelatihan, Reward, dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT Metal Hitech Engineering - Firnanda, Novia; Baskoro, Heru (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the effect of training, rewards, and work environment on employee performance at PT Metal Hitech Engineering. In an era of ever-changing business, it is important for companies to improve the quality of human resources in order to compete effectively. The method used in this study is a quantitative approach with data collection through questionnaires distributed to employees. The sample taken was 64 respondents with a nonprobability sampling technique. The data analysis technique used was multiple linear regression analysis and partial hypothesis testing (t-test) using SPSS 25. The results of the study showed that the independent variable, namely training (X1) partially did not have a significant effect on employee performance (Y), while the Reward (X2) and Work Environment (X3) variables partially had a significant effect on employee performance (Y). The conclusion of this study confirms that to improve employee performance, companies need to optimize training programs, provide appropriate rewards, and create a conducive work environment. This study is expected to be a reference for companies in formulating strategies to improve employee performance and provide insight for further research that is relevant to this topic.